Preparation of Mesoporous γ-al2o3 with High Surface Area from an Alooh Extract of Recycling Biomass Ash - Pizarro-Konczak, J; Castillo-Castillo, X; Gómez-Barrena, M; Diaz-Navarro, C (Elsevier Ltd, 2021)
This study explores the potential application of recycled materials extracted from arboreal ABA (ABA); this waste is used as an alternative source of aluminium oxyhydroxide for the synthesis of γ-Al2O3 with high surface area-based mesoporous materials with interesting applications in environmental remediation. The aluminium present in ABA was extracted by desilication and reflux in acid and subsequently converted to mesoporous γ-Al2O3 via a sol–gel process with Pluronic P-123 as surfactant. The surface of that material was successfully functionalized with racemic glycine (GLY) and N,N-dimethylacetamide (DMAC) by liquid impregnation in order to study and compare their applications in capture of Fe3+ cations. All the materials were unambiguously characterized by adsorption-desorption isotherms of N2 at 77 K, X-ray fluorescence (XRF), elemental analysis (EA), X-ray diffraction (XRD), diffuse reflectance infrared fourier transform spectroscopy (DRIFTS), scanning electron microscopy with dispersive energy detector of X-ray (SEM-EDS), transmission electronic microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). This process afforded γ-Al2O3 with high purity and the surface area of the mesoporous materials ranged from 115 m2 g−1 for AlOOH to 230 m2 g−1 for γ-Al2O3. The achieved surface functionalization was of 2 and 3 wt% with glycine and DMAC, respectively. The effective performance of these materials (both pristine and functionalized) in the removal of Fe3+ ions from an aqueous solution was evaluated in batch systems. In particular, the materials presented extraction capacities of about 78.2% for bare γ-Al2O3, 83.2% for Al-GLY and 93.9% for Al-DMAC. © 2021 Elsevier Ltd